1994
DOI: 10.3758/bf03200778
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subject performance during the semester: An empirical investigation

Abstract: Two experiments were conducted to probe for performance differences between early-semester subjects and late-semester subjects in an introductory psychology subject pool. In Experiment 1A, hypotheses regarding changes in performance included differential effort, changes in subjects' attention to the task, and changes in subjects' sensitivity. A signal detection paradigm was used, and 278 subjects were sampled over the course of the semester. No evidence of changes in subject performance was found, in spite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…We found that repeated attitude expression decreased attitude importance (marginally significantly), whereas Roese and Olson (1994) found that repeated expression increased importance. Past studies have shown that attitude processes sometimes differ across attitude objects (e.g., Prislin, 1996;Wallsten, 1996) and across participant populations (e.g., Langston et al, 1994), and the discrepancy in our case may be due to an interaction of these two factors.…”
Section: Explaining Divergence Between Studiescontrasting
confidence: 45%
“…We found that repeated attitude expression decreased attitude importance (marginally significantly), whereas Roese and Olson (1994) found that repeated expression increased importance. Past studies have shown that attitude processes sometimes differ across attitude objects (e.g., Prislin, 1996;Wallsten, 1996) and across participant populations (e.g., Langston et al, 1994), and the discrepancy in our case may be due to an interaction of these two factors.…”
Section: Explaining Divergence Between Studiescontrasting
confidence: 45%
“…The time of day that subjects are tested in multisession experiments can produce significant session effects. It is widely believed that subjects tested at the beginning of an academic semester or quarter can give very different data from those tested near the end (but see Langston, Ohnesorge, Kruley, & Haase, 1994). In the case where parameters change over blocks of trials, Burbeck and Luce (1982) have discussed a method whereby blocks with highly deviant parameters can be eliminated.…”
mentioning
confidence: 99%
“…This decrement appears in interview question formation and impression formation (Casa de Calvo & Reich, 2007), visual search (Richert & Ward, 1976), and serial learning and symbol substitution (Richter et al, 1981). In contrast, tasks that might not require as much flexibility should not show end of semester decrements, as has been documented for a hidden figures task (Richert & Ward, 1976), cued recall (Wang & Jentsch, 1998), and signal detection (Langston, Ohnesorge, Kruley, & Haase, 1994). …”
Section: Discussionmentioning
confidence: 82%